Cédric Martigny, la photographie au travail - Caroline Bach (Images du Travail, Travail des Images)
Based on the photographic practice of Cédric Martigny, this article focuses on the representation of work through photography. Through several photographic series, I will analyze two operational modes set up by the photographer : decontextualization and transfiguration. These two processes allow the photographer to rely on the worker's clothes and gestures to elaborate photographic settings and to speak about the worker’s body. More generally, they will also allow me to analyze the place and the role of the photographer in these different series.